Correlations between the national urbanised areas and the recreational spaces - Hegedüs, Veronika (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
Hungarian urbanised areas are characterised by their unique geographical processes, resulting in significant spatial alterations. These characteristics can be derived from the changes – through history – of the settlement structure, economic, infrastructural and environmental features and the social characteristics. These features in the urbanised spaces resulted in the formation and completion of „modernised” life circumstances. Recreational areas and activities formed an increasingly important element of these processes. Oriented to the spatial differences of urbanised spaces, the presence of leisure areas also shows significant differences. In Transdanubia and Northern Hungary, where the dominance of small and medium sized cities is peculiar, more preferably the active areas around the settlement (areas outside the administrational boundary of the settlement) can be stressed (e.g. Miskolc-Mályi, Sopron-Fertőrákos). Here the motivation of recreational activities is mainly natural attractions. In the area of the Great Hungarian Plain (Alföld) – where greater cities maintain a considerable role – recreational zones are formed mainly within the administrational boundaries of the settlements (e.g. Debrecen-Nagyerdő). Here cultural and special features have a bigger role from the motivations. Of course the recreational zones deriving from settlement geographical specialities can not be left out of consideration where the motivational role of natural attractions (e.g. the small settlements around Nyíregyháza) is having a greater emphasis. The special features of the Great Plains can mainly be explained by their former development which significantly altered their urbanisation. The recreational needs of the local societies are oriented to this altered development. This is proved by the dominance of „second homes” and hobby farms in the mentioned areas.